Immunological Mechanisms in Allergic Diseases and Allergen Tolerance: The Role of Treg Cells - D. Calzada; S. Baos; L. Cremades-Jimeno; B. Cárdaba (Journal of Immunology Research)
The immune system regulates itself to establish an appropriate immune response to potentially harmful pathogens while tolerating harmless environmental antigens and self-antigens. A central role in this balance is played by regulatory T cells (Tregs) through various ways of actions. By means of molecule secretion and cell-cell contact mechanisms, Tregs may have the capacity to modulate effector T cells and suppress the action of proinflammatory cytokines across a broad range of cell types. As a result, abnormal regulatory T cell function has been pointed as a main cause in the development of allergic diseases, a major public health problem in industrialized countries, with a high socioeconomic impact. This prevalence and impact have created an international interest in improving the allergy diagnosis and therapy. Additionally, research has sought to gain a better understanding of the molecular mechanisms underlining this kind of disease, in order to a better management. At this respect, the role of Treg cells is one of the most promising areas of research, mainly because of their potential use as new immunotherapeutical approaches. Therefore, the aim of this review is to update the existing knowledge of the role of Tregs in this pathology deepening in their implication in allergen-specific therapy (AIT).